2002
DOI: 10.1002/jemt.10198
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of chemoreceptor elements in the carotid body

Abstract: The electrical properties of chemoreceptor afferent nerve fibers and glomus cells and the behavior of cytosolic Ca(2+) in glomus cells are reviewed. While this has not been confirmed, spontaneously depolarizing potentials (SDPs) recorded in a chemoreceptor afferent terminal may be the postsynaptic expression of presynaptic events. Glomus cells, which are presynaptic elements, either depolarized or hyperpolarized in response to natural and chemical stimulation. After-hyperpolarization following an initial depol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…There are several recent reviews of various aspects of the function of, and signaling in, carotid body cells (147,163,212,241). The carotid body, the primary site of peripheral chemoreception, has two types of cells: catecholamine-containing type I cells (glomus cells) and type II cells (sustentacular cells), which are like glial cells.…”
Section: Other Acid-sensitive Cellsmentioning
confidence: 99%
“…There are several recent reviews of various aspects of the function of, and signaling in, carotid body cells (147,163,212,241). The carotid body, the primary site of peripheral chemoreception, has two types of cells: catecholamine-containing type I cells (glomus cells) and type II cells (sustentacular cells), which are like glial cells.…”
Section: Other Acid-sensitive Cellsmentioning
confidence: 99%
“…We could therefore conclude that despite the presence of symmetrical junctions (desmosomes) between glomus cells (Hess, 1975; Abudara et al . 2002; Hayashida & Hirakawa, 2002) the electrogenic coupling that might have been expected to unify the response possibly in all the cells of the same cluster did not take place.…”
Section: Methodsmentioning
confidence: 99%
“…Although most studies have found that glomus cell [Ca 2+ ] i increases as P O 2 is lowered, some have reported that a substantial proportion of glomus cells do not respond to hypoxia (Bright et al, 1996; Hayashida and Hirakawa, 2002). A common feature of these studies is the use of mild hypoxia challenge (superfusate P O 2 ~ 35–38 mmHg) which, based on the [Ca 2+ ] i - P O 2 relationship from multiple studies, would be expected to cause either a small or no [Ca 2+ ] i rise in dissociated glomus cells (Fig.…”
Section: 0 Developmental Profile Of Isolated Carotid Body Glomus Cellsmentioning
confidence: 99%
“…Four studies have reported that [Ca 2+ ] i may increase or decrease in response to hypoxia in glomus cells from adult rat or mouse (Donnelly and Kholwadwala, 1992; Hayashida et al, 2000; Wotzlaw et al, 2011; Zhang and Eyzaguirre, 1999). One of these studies employed imaging of glomus cells in-situ in the intact, adult mouse CB and the other used minimally-disrupted clusters of glomus cells from adult rats, suggesting that [Ca 2+ ] i responses of glomus cells in-situ may differ from dissociated cells (Hayashida and Hirakawa, 2002; Hayashida et al, 2000; Wotzlaw et al, 2011). Further study will be required to determine whether such heterogeneity of glomus cell [Ca 2+ ] i responses is characteristic of the adult, associated with to cell-cell interactions or related to methodology or other factors.…”
Section: 0 Developmental Profile Of Isolated Carotid Body Glomus Cellsmentioning
confidence: 99%